HUBUNGAN PENGETAHUAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PASIEN SKIZOFRENIA DI POLIKLINIK RUMAH SAKIT PROF. V.L. RATUMBUYSANG MANADO - Purnamasari, Natalia; Tololiu, Tinneke; Pangemanan, Damajanty H.C. (JURNAL KEPERAWATAN)
Abstract: Schizophrenia is a disease that affects the brain and of cause the emergence of thoughts, perceptions, emotions, movement, and behavior strange and disturbed. Schizophrenia can not be defined as a disease in it self, but is suspected as a syndrome or disease process that includes many types with a variety of symptoms. This study was conducted to determine the relationship of the family with knowledge of drug compliance in schizophrenic patients using descriptive correlative design with cross-sectional research design. As the design of the study. Instrument is made in the form of questionnaires and divided into 2 parts, namely the family to measure knowledge about the treatment of patients with schizophrenia and measure medication adherence in patients with schizophrenia using a Guttman scale. Number of samples in as many as 50 people carefully using proposive sampling as data capture techniques. The results illustrate that there is no good knowledge about the treatment of schizophrenic patients, 36% of respondents have sufficient knowledge regarding the treatment of patients with schizophrenia, 48% of respondents have less knowledge about the treatment of schizophrenic patients. Statistical analysis with Spearman rho degrees of freedom (Î±) = 0.01 is obtained and the value of p= 0.000 for the relationship of knowledge with compliance, there is a significant relationship between knowledge monum medication adherence of patients with schizophrenia. Suggestions for nursing practice are expected to conduct supervision and monitoring of the application of the empowerment of the family in the provision of nursing care on the family. Key words: knowledge, the family, compliance, schizophrenia Abstrak: Skizofrenia adalah penyakit yang mempengaruhi otak dan penyebabkan timbulnya pikiran, persepsi, emosi, gerakan, dan perilaku yang aneh dan terganggu. Skizofrenia tidak dapat didefinisikan sebagai penyakit tersendiri, melainkan diduga sebagai suatu sindrom atau proses penyakit yang mencakup banyak jenis dengan berbagai gejala. Penelitian ini dilakukan untuk mengetahui hubungan pengetahuan keluarga dengan kepatuhan minum obat pasien skizofrenia dengan menggunakan desain deskriptif korelatif dengan rancangan penelitian Cross Sectional. Sebagai desain penelitian. Instrument dibuat dalam bentuk kuesioner dan dibagi dalam 2 bagian, yaitu bagian untuk mengukur pengetahuan keluarga tentang pengobatan pasien skizofrenia dan bagianuntuk mengukur kepatuhan minum obat pasien skizofrenia dengan menggunakan skala guttman. Jumlah sampel yang di teliti sebanyak 50 orang dengan menggunakan proposive sampling sebagai teknik pengambilan data. Hasil penelitian menggambarkan bahwa tidak ada yang berpengetahuan baik mengenai pengobatan pasien skizofrenia, 36% responden memiliki pengetahuan cukup mengenai pengobatan pasien skizofrenia , 48% responden memiliki pengetahuan kurang mengenai pengobatan pasien skizofrenia. Analisa statistic spearman rho dengan derajat kebebasan (Î±) = 0,01 diperoleh nilai p = 0,000 untuk hubungan pengetahuan dengan kepatuhan, terdapat hubungan yang signifikan antara pengetahuan dengan kepatuhan monum obat pasien skizofrenia. Saran untuk praktek keperawatan diharapkan dapat melakukan superviseÂ  dan monitoring terkait penerapan pemberdayaan keluarga dalam pemberian asuhan keperawatan pada keluarga. Kata kunci: Pengetahuan, Keluarga, Kepatuhan, Skizofrenia